Pharmacists' Attitudes towards Medically Assisted Dying - Lun Shen Wong; Shane L. Scahill; Emma Barton; Bert Van der Werf; Jessica Boey; Sanyogita (Sanya) (MDPI AG, 2024)
Aims: We aimed to explore pharmacists' attitudes and support toward medically assisted dying (MaiD) through the End of Life Choice Act 2019 (EOLC), their willingness to provide services in this area of practice, and the influences on their decisions. Methods: The study was conducted via an anonymous, online QualtricsTM survey of pharmacists. Registered New Zealand pharmacists who agreed to receive surveys from the two Schools of Pharmacy as part of their Annual Practicing Certificate renewal were invited to participate through an email with a Qualtrics URL link. The survey contained questions regarding demographics, awareness, knowledge, support for, and attitudes and willingness to participate. Results: Of the 335 responses received, 289 were valid and included in the analysis. Most participants supported legally assisted medical dying (58%), almost a third of participants did not support it (29%), and 13% of respondents were unsure. The five primary considerations that participants perceived to be beneficial included support from legislation, respect for patient autonomy, discussions around morality, ending suffering, and preserving dignity. The main concerns were legal, personal bias, palliation, stigmatisation, and vulnerability. Conclusions: The influences on the decision by pharmacists to support and willingness to participate in the provision of services consistent with the EOLC are complex and multifactorial. Diverse factors may influence attitudes, of which religion is the most significant factor in not supporting the Act or willingness to participate. Clarity and standardised guidance to ensure that assisted dying queries are appropriately managed in practice would help to address any potential access issues.